Penggetasan Logam Cair pada Capillary Tube Baja Tahan Karat 316 - Apriardi Ihlas (Center for Material and Technical Product, 2015)
A capillary tube is a component that serves the chemical solution (scale inhibitor) into the oil wells, which could potentially form the crust. There have been obstructions (clogging) and cracks in the capillary tube components made from austenitic stainless steel 316. The installation of these components is in one unit with another component called “centriline cel flat”. To know more about the cause of the occurrence of the damage, a series of inspection and testing was carried out.The inspection included: initial data and chronology, visual, metallography (macro and micro), and Scanning Electron Microscopy/ Energy Dispersive X-ray Spectroscopy (SEM-EDS). The result of the inspection suggested that a penetration of zinc on the surface of the tube existed. The penetration of zinc melting up to the grain limit will form zinc-nickel intermetallic compounds that will result in a change of austenite into a ferrite phase. The internal stress changes due to changes in the phase volume is the cause of the occurrence of cracks at grain boundary.Capillary tube adalah komponen yang berfungsi mengalirkan larutan kimia (scale inhibitor) ke dalam sumur minyak yang berpotensi membentuk kerak. Telah terjadi penyumbatan (clogging) dan retak-retak pada komponen capillary tube yang berbahan baja tahan karat austenit 316. Pemasangan komponen tersebut berada dalam satu kesatuan unit dengan komponen lain yang bernama centriline cel flat. Untuk mengetahui lebih lanjut penyebab terjadinya kerusakan, dilakukan serangkaian pemeriksaan dan pengujian. Pemeriksaan tersebut meliputi: data awal dan kronologi, visual, metalografi (makro dan mikro), dan Scanning Electron Microscopy/ Energy Dispersive X-ray Spectroscopy (SEM-EDS). Hasil pemeriksaan menunjukkan adanya penetrasi seng pada permukaan tube. Penetrasi seng yang mencair mencapai batas butir akan membentuk senyawa intermetallic seng-nikel yang akan mengakibatkan terjadinya perubahan fasa austenit menjadi ferit. Perubahan internal stress akibat perubahan volum fasa inilah yang menyebabkan terjadinya retakan di batas butir.